A therapeutic roadmap for ovarian cancer using TLR4 MyD88 and MAD2 as prognostic indicators - Bates, Mark (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2016)
Ovarian cancer is 4th leading cause of cancer death in woman and the most lethal gynaecological malignancy. Most patients present with advanced disease where the 5 year survival rate is less than 40%. Standard treatment for advanced ovarian cancer includes cytoreductive surgery followed by paclitaxel/carboplatin based chemotherapy. However despite the use of these front line chemotherapeutic agents, mortality rates for ovarian cancer have remained almost unchanged for the past 30 years. A major reason for this poor prognosis is the development of chemoresistance and recurrent disease. Therefore there is a dire need for prognostic biomarkers which can predict patient response to chemotherapy from the outset and prevent the development of chemoresistant recurrent disease. Currently there are no reliable prognostic markers in routine use for ovarian cancer. In this study we investigated the role of three protein biomarkers TLR4, MyD88 and MAD2 in ovarian cancer. High TLR4 and MyD88 expression and low MAD2 expression have been associated with poor survival and paclitaxel resistance in-vitro. The aim of this project was to assess the combined utility of these three markers in predicting patient prognosis and to investigate any potential in-vitro link between these three markers and the paclitaxel resistance mechanisms in which they are involved.
Embargo End Date: 2023-07-01
Keywords: Histopathology and Morbid Anatomy, Ph.D.; Ph.D. Trinity College Dublin, 2016